2011
DOI: 10.1089/tmj.2011.0083
|View full text |Cite
|
Sign up to set email alerts
|

Video-Telemedicine in a Memory Disorders Clinic: Evaluation and Management of Rural Elders with Cognitive Impairment

Abstract: VTM is emerging as an effective way to provide consultation and care to rural residents who may not have access to specialty services and can be integrated into current clinical settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 21 publications
2
69
0
4
Order By: Relevance
“…The factor loading for item 4, regarding ease of getting to the telehealth department (0.54) was lower than for other items, but still well above recommended cut-offs. 31 Compared to earlier studies examining satisfaction with telemedicine in memory clinic settings, [16][17][18] this study includes a larger sample size (n = 223 vs. 11, 15, and 99 respectively) and provides evidence of scale reliability and validity. Results from our previous analyses of telehealth in the RRMC provided additional evidence for the validity of the TeSS.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…The factor loading for item 4, regarding ease of getting to the telehealth department (0.54) was lower than for other items, but still well above recommended cut-offs. 31 Compared to earlier studies examining satisfaction with telemedicine in memory clinic settings, [16][17][18] this study includes a larger sample size (n = 223 vs. 11, 15, and 99 respectively) and provides evidence of scale reliability and validity. Results from our previous analyses of telehealth in the RRMC provided additional evidence for the validity of the TeSS.…”
Section: Discussionmentioning
confidence: 93%
“…Azad et al 16 did not report overall satisfaction scores, but 92% of participants were satisfied with the session, and 95% would use videoconferencing again. The informal feedback collected by Barton et al 17 indicated patient and provider satisfaction with the neurological and cognitive assessment conducted via telehealth. Poon et al 18 evaluated a 12-session cognitive assessment and intervention program delivered by videoconferencing or face to face.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Телепатронаж (как форма пациент-центрированной телемедицины) наиболее эффективен у пациентов с деградацией когнитивной функции 276 , особенно проживающих в районах с низ-кой плотностью населения. При этом комбинированно применяются телефония, программные видеоконференции и специализированные веб-сайты (для дистанционного обучения и ин-формирования как самих пациентов, так и лиц, оказывающим непосредственный уход и по-мощь).…”
Section: балльная оценка = (возраст * 02) + 6 (если в анамнезе фибриunclassified